The effect of stepwise acupuncture on cognition, insomnia, and tremors after traumatic brain injury: a case report - Ting-Yu Huang; Che-Pin Chang (Journal of Medical Case Reports)
Abstract Background This report focused on the effect of acupuncture on the recovery of patients with traumatic brain injury, which is a suggested therapy to help improve consciousness and prognosis. Case summary The patient was a 69-year-old Taiwanese male who suffered from traumatic brain injury and multiple traumas (Injury Severity Score of 24). This patient provided informed consent. After his initial injury, he underwent acupuncture therapy at our hospital continuously for 1.5 months. Throughout the different phases, he experienced disorientation, agitation, insomnia, Holmes tremors, and dizziness; therefore, he received acupuncture at the following acupoints: GV20, BL7, GB8, GV24, GB13, ST8, LI11, LI4, TE5, GB34, LV3, SP6, LV2, and KI7. In addition, he received Jiao’s scalp acupuncture six times per week, depending on his stage. After he received the stepwise acupuncture therapy, he recovered consciousness, had no tremors, and could walk under supervision only 3 months after the initial accident. Conclusion A stepwise acupuncture approach using different acupoints during different phases of recovery was associated with the speedy recovery of this patient with traumatic brain injury and multiple traumas. This case also highlights the applicability of acupuncture to the treatment of Holmes tremor.